Identification of potent epitopes on hexon capsid protein and their evaluation as vaccine candidates against infections caused by members of Adenoviridae family. Issue 27 (16th June 2021) - Tufail, Soban; Shah, Majid Ali; Zafar, Maryam; Asif, Tayyab Ali; Shehzad, Aamir; Shah, Muhammad Salahuddin; Habib, Mudasser; Saleemi, Muhammad Kashif; Muddassar, Muhammad; Mirza, Osman; Iqbal, Mazhar; Rahman, Moazur
Graphical abstract: Highlights: Identification of a potent epitopic region on hexon proteins of adenoviruses. The epitopic region generates a strong immune response in fusion with HBc. The HBc-fused epitope confers 90% protection against FAdV-4 in chickens. The epitopic region could be used as a VLP vaccine against adenoviral infections. Abstract: Adenoviruses cause economically important diseases in vertebrates. Effective vaccines against adenoviral diseases are currently lacking. Here, we report a highly conserved epitopic region on hexon proteins of adenoviruses that generate a strong immune response when used as a virus-like-particle (VLP) vaccine, produced by inserting the epitopic region into the core protein of hepatitis B virus. For evaluation of its protective efficacy, the epitopic region from a representative adenovirus, fowl adenovirus serotype 4 (FAdV-4), was tested as a VLP vaccine which conferred 90% protection against challenge with a virulent FAdV-4 isolate in chickens. Importantly, such a high level of protection is not achieved when the epitopic region is employed as a part of a subunit vaccine. As the sequence and the structure of the epitopic region are highly conserved in hexon proteins of adenoviruses, the epitopic region could be employed as a promising VLP vaccine candidate against adenoviral diseases, in general.